What "hides" behind sovereign debt ratings? - Afonso, António (2010)
In this paper we study the determinants of sovereign debt credit ratings using rating notations from the three main international rating agencies, for the period 1995-2005. We employ panel estimation and random effects ordered probit approaches to assess the explanatory power of several macroeconomic and public governance variables. Our results point to a good performance of the estimated models, across agencies and across the time dimension, as well as a good overall prediction power. Relevant explanatory variables for a country's credit rating are: GDP per capita, GDP growth, government debt, government effectiveness indicators, external debt, external reserves, and default history.